2019
DOI: 10.1016/bs.mie.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unknown Metabolomics Mixture Compounds by Combining NMR, MS, and Cheminformatics

Abstract: Metabolomics aims at the comprehensive identification of metabolites in complex mixtures to characterize the state of a biological system and elucidate their roles in biochemical pathways. For many biological samples, a large number of spectral features observed by NMR spectroscopy and mass spectrometry (MS) belong to unknowns, i.e. these features do not belong to metabolites that have been previously identified, and their spectral information is not available in databases. By combining NMR, MS, and combinator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Interestingly, corresponding outputs only partially overlap in terms of detected metabolites, and both technologies that offer complementary advantages and disadvantages [ 37 ] have proven to deliver robust results for metabolomics studies. Recent advances tend to associate MS and NMR through integrated studies to maximize the sensitivity and precision of metabolomics studies [ 34 , 38 , 39 ]. The information-rich datasets generated from NMR or MS are subjected to computational and statistical analyses to identify event-related metabolite changes and potential biomarkers [ 40 ].…”
Section: Metabolic Phenotyping Of Cell Culture Metabolism: Analytimentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, corresponding outputs only partially overlap in terms of detected metabolites, and both technologies that offer complementary advantages and disadvantages [ 37 ] have proven to deliver robust results for metabolomics studies. Recent advances tend to associate MS and NMR through integrated studies to maximize the sensitivity and precision of metabolomics studies [ 34 , 38 , 39 ]. The information-rich datasets generated from NMR or MS are subjected to computational and statistical analyses to identify event-related metabolite changes and potential biomarkers [ 40 ].…”
Section: Metabolic Phenotyping Of Cell Culture Metabolism: Analytimentioning
confidence: 99%
“…Yet, a large proportion of MS signals remain unidentified. Recent strategies combining NMR and MS show a strong potential for the identification of the unknowns [ 38 , 98 ].…”
Section: Metabolic Phenotyping Of Cell Culture Metabolism: Analytimentioning
confidence: 99%
“…The second category is related to the research of new unknown biomarkers. In this latter case, untargeted metabolomics would require multiple complementary analytical approaches to characterize the unknown molecule(s) 97,98 . Another emerging field in life sciences and biomedical research is the characterization of the relationship between gut microbiota metabolome and health/disease 99–101 .…”
Section: Main Applications Of Steady‐state Metabolomicsmentioning
confidence: 99%
“…In this latter case, untargeted metabolomics would require multiple complementary analytical approaches to characterize the unknown molecule(s). 97,98 Another emerging field in life sciences and biomedical research is the characterization of the relationship between gut microbiota metabolome and health/disease. [99][100][101] For instance, it has been also demonstrated that human gut microbiota homeostasis has a direct impact on host serum metabolomic profile, insulin sensitivity, and neurotransmitters abundance.…”
Section: Main Applications Of Steady-state Metabolomicsmentioning
confidence: 99%
“…However, these methods are not effective for unknown molecules whose spectra are not registered in the database. In addition, even for prediction methods based on computational chemistry [ 17 ] and machine learning [ 18 20 ], NMR spectra cannot be calculated without the structures of the compounds; thus, these methods are also not useful for unknown molecules [ 21 , 22 ]. In this work, we try to identify unknown molecules from its NMR spectrum with a de novo molecule generator.…”
Section: Introductionmentioning
confidence: 99%